Nanotechnology in COVID-19 Diagnosis and Treatment: A Bibliometric Analysis (Bangladesh Pharmaceutical Journal, 2022)
There is an utmost urgency of having new and advanced diagnostics as well as therapeutic alternatives along with the conventional methods to treat coronavirus disease 2019 (COVID-19). For this purpose, different strategies must be explored for the advancement of testing capacity, developing effective treatments, and developing safe vaccines that provide long-term immunity. Nanotechnology has been found effective against COVID-19 in terms of diagnosis, prevention, and treatment. The diameter of SARS-CoV-2 (60–140 nm) is similar to nanoparticles. This is why, synthetic nanoparticles can precisely resemble SARS-CoV-2, and efficiently interact with the viral proteins and counter this virus. Nanotechnology offers benefits by developing efficient and cost-effective diagnosis methods and facilitating the improvement of drug properties through nano-carriers, namely liposomes, micelles, metallic nanoparticles, etc. The bibliometric analysis evaluates scholarly contributions using mathematical and statistical methodologies. In this study, the bibliometric analysis investigated the publication trends of nanoparticles and their application in COVID-19 diagnosis and treatment. We have systematically searched the different search engines and publishers (Scopus, PubMed, and Google scholar) from 2020 to 2021, and various visual maps were generated to show, the most- relevant authors, sources, countries, topics, and keywords by using a software called VOSviewer. The findings indicate the advancement of nanotechnology in the diagnosis and therapy of COVID-19. At last, the bibliometric analysis of nanoparticles for COVID-19 diagnosis and treatment provides a clear view of the future research directions and identifies the potential challenges and opportunities. This may pave the way for new researchers to find the proper subfields in nanoparticle-related research areas for combating the COVID-19.Bangladesh Pharmaceutical Journal 25(2): 199-208, 2022 (July)